Perlindungan Hukum terhadap Konsumen dalam Penggunaan Styrofoam Yang Digunakan Pada Kemasan Makanan di Kecamatan Sail Kota Pekanbaru Dikaitkan Dengan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Putra, Try Alda; Fitriani, Riska; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law Number 8 Year 1999 About Consumer Protection Is Legal Basis in Legal Protection AgainstConsumers In The Use Of Styrofoam On Food Packaging In Sail Sub-District Pekanbaru Is Associated WithLaw Number 8 Year 1999 About Consumer Protection. The Need for Legal Protection of Consumers in the Useof Styrofoam in Food Packaging is due to the many business actors who use Styrofoam as food packaging inSail Sub-district Pekanbaru City, which became one of the problems that have a major impact on consumerhealth. Therefore, the purpose of this thesis writing, namely: First, knowing consumer knowledge and businessactors on consumer health on the use of styrofoam by business actors as packaging on food; Secondly, to knowthe legal protection of the consumers regarding the use of Styrofoam products as food packaging in Sail Sub-District in Pekanbaru City related to Law Number 8 Year 1999 About Consumer Protection.This type of research can be classified in the type of legal juridical sociological research, referred tosociological juridical research is the approach by looking in terms of legislation and the reality that occurredin the field, In accordance with the formulation of the problems expressed by the author. This research wasconducted in Pekanbaru City, at Central Office of Food and Drug Monitoring Riau Province, and in DistrictSail. Population and Sample are. Food traders and food buyers. Sources of data used, namely: primary dataand secondary data. Data collection techniques in this study with questionnaires, interviews, and literaturereview.The conclusions can be obtained from the results of research is First, Consumer Knowledge andBusiness Actors Consumer Health on the Use of Styrofoam as Packaging in Food Business and Consumer Donot Know Overall; Second, inhibiting factors, ineffective implementation of the purpose of consumer protectionand causing harm to consumers in the use Styrofoam the disease suffered in the future. The author's suggestionis to the central government to make regulations regarding the prohibition on the use of Styrofoam in foodpackaging. And the Local Government and the Agency BPOM to give special attention in the use of Styrofoamused in food packaging. and To business actors to raise awareness about the importance of consumerprotection and improve the quality of goods and / or services that ensure the continuity of goods and / orservices production, health, convenience, security and consumer safety, and for consumers to increaseawareness, ability and independence to protect themselves.Keywords: Use of Styrofoam-a health hazard-in Sail District.